Environmental Education: Revealing Some Current Problems from Personal Opinion - Hsu, Chia-Hsuan (Technium Social Sciences Journal, 2021)
Air and water pollution, wildlife habitat loss, soil desertification, and other environmental problems affect cities and the surrounding environment. Thus, increasing public environmental awareness and environmental literacy are essential for mitigating these problems. Although environmental education has been critical in solving problems that affect humans and the environment for more than five decades, the question remains whether the environment is improving or being degraded. Educators are devoted to popularizing environmental education, but as a result of many problems, people are gradually becoming paralyzed. Efficient methods of motivating people to perform environmentally friendly behaviors are required. Moreover, the term “environmental education” has been abused in some situations to receive government benefits. Thus, as an environmental educator and researcher, I provide opinions and reveal problems in environmental education.